ANALISIS LIKUDITAS DAN PROFITABILITAS SEBAGAI ALAT UNTUK MENGUKUR KINERJA KEUANGAN PADA PT POS INDONESIA (PERSERO) - Nopiana, Puspita Rama; Br Pinen, Fanny (Aksara Public, 2017)
The purpose of this study were 1) the financial performance of PT Pos Indonesia (Persero) using liquidity analysis, 2) the financial performance of PT Pos Indonesia (Persero) using profitability analysis, 3) efforts to improve financial performance by PT Pos Indonesia (Persero). Results of the study 1) financial performance measured using liquidity analysis to: a) Current ratio has a percentage of 107.80%, this result is not good or illiquid, b) Cash ratio has a percentage of 85.97%, this result is good or illikuid c) Quick ratio percentage of 107.76% was also said to be good. 2) financial performance measured using profitability analysis results: a) Return On Assets (ROA) have a percentage of 3.80%, providing information that its financial performance does not efisien. b) Return On Equity (ROE) has a percentage of 20, 90%, explained in terms of financial performance ROE efficient. 3) efforts to improve the financial performance of the company in the form of: a) the increase in revenues from the fields of business, b) the achievement of the performance improvement company in a sustainable manner, c) maintain good corporate governance (GCG) according to standard best practice are guided by principles base, d) shaping the performance of cooperation, in which the Commissioner ensure thorough supervision over all activities of the company, helped by the role of the Audit Committee and Business Risk Management oversight Committee and Investment. e) Monitoring is always done the Board in monitoring the company's activities primarily on corporate social responsibility (CSR).